Secret Seven (Look Out, Secret Seven) - Blyton, Enid; Hamilton, Dorothy (London Award Publications Limited, 1992)
What would the Seven do without Scamper the spaniel? First he discovers an unwanted visitor - then he protects the Seven as they spy on a thief late at night in Bramley Woods.